Silver Doped TiO2 Photocatalyst for Disinfection of E. coli and Microplastic Pollutant Degradation in Water - Haris, M.F.; Didit, A.M.; Ibadurrohman, M.; Setiadi; Slamet (Asian Journal of Chemistry, 2021)
Present study report the synthesis of Ag/TiO2 catalyst to study its ability to disinfect the pathogenic microorganisms and degrade into micropollutants in water. The Ag/TiO2 was synthesized by photoassisted deposition (PAD) method. The ratio of silver dopant varied (1%, 3% and 5%) to the total weight of the composite. The SEM-EDX, UV-Vis DRS and XRD techniques were used to characterize and determine the influence of silver dopant on the TiO2 structure. In this study, the microorganism used was Escherichia coli and the microplastic used was polyethylene. During the photocatalytic process under ultraviolet light irradiation, a magnetic stirrer was used at 2000 rpm. The performance of photocatalyst in E. coli disinfection and microplastic degradation improved by the addition of silver dopant. The 3% silver dopant has optimum performance with 79% of microbial disinfection within 2 h and 81% microplastic degradation within 4 h.